2022
DOI: 10.1016/j.aohep.2022.100684
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of hepatitis B and C viruses in moderate and severe COVID-19 inpatients: A cross-sectional study at a referral center in Mexico

Abstract: Introduction and Objectives : The emergence of SARS-CoV-2, which causes the coronavirus disease (COVID-19) has caused a great impact on healthcare systems worldwide, including hepatitis B and C viruses screening and elimination programs. The high number of COVID-19 hospitalizations represent a great opportunity to screen patients for hepatitis B virus (HBV) and hepatitis C virus (HCV), which was the aim of this study. Material and Methods : Cross-sectional, retrospectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
4

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 11 publications
0
4
0
4
Order By: Relevance
“…Regarding the treatment of choice for SARS-CoV-2 infection, the immunosuppressants and corticosteroids used to treat the infection are considered to be at high risk of HBV reactivation, which highlights the importance of screening for the disease at the time of hospitalization of patients infected with SARS-CoV-2. 13 A study carried out in Spain points out that screening for hepatitis B in patients hospitalized with COVID-19 was necessary, given the risk of drug reactivation. The results of this cross-sectional study showed HBV reactivation in 14.2% of patients who did not use entecavir prophylaxis during treatment with immunosuppressants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the treatment of choice for SARS-CoV-2 infection, the immunosuppressants and corticosteroids used to treat the infection are considered to be at high risk of HBV reactivation, which highlights the importance of screening for the disease at the time of hospitalization of patients infected with SARS-CoV-2. 13 A study carried out in Spain points out that screening for hepatitis B in patients hospitalized with COVID-19 was necessary, given the risk of drug reactivation. The results of this cross-sectional study showed HBV reactivation in 14.2% of patients who did not use entecavir prophylaxis during treatment with immunosuppressants.…”
Section: Discussionmentioning
confidence: 99%
“…Investigates the seroprevalence of hepatitis B and C viruses in patients hospitalized with COVID-19 in Mexico. 13 Evaluates the effects of the hepatitis B virus on the body of patients infected with COVID-19. 14 Investigates possible reactivation of HBV triggered by SARS-CoV-2 infection.…”
Section: Thematic Considerationsmentioning
confidence: 99%
“…Si bien las coinfecciones virales más frecuentemente identificadas corresponden a patógenos virales respiratorios como el virus sincitial respiratorio o virus de influenza A (19) , existe evidencia de coinfección de SARS-CoV-2 con VHB, VHC o VIH (17,18) , razón por la que debe considerarse el efecto que la coinfección con estos virus podría derivar en los pacientes. Diversos autores han reportado casos de reactivación de VHB en pacientes con SARS-CoV-2 (20)(21)(22) así como de reactivación de VHS (23) . En este sentido, parece contradictorio que haya riesgo de reactivación viral en una enfermedad como la COVID-19 que se caracteriza por la predisposición a un alto estado inflamatorio como lo es la tormenta de citoquinas, no obstante, es un hecho factible puesto que precisamente por el riesgo asociado con la tormenta de citoquinas, se emplean diversas terapias inmunomoduladoras que se han relacionado con el riesgo de reactivación viral (23)(24)(25) .…”
Section: Introductionunclassified
“…As one of the most widespread infectious diseases in the world, the prevalence of chronic HBV infection shows a different geographical distribution. The global seroprevalence of HBsAg was reported to be 3.61% with high prevalence (> 8.00%) in countries of the African region (about 8.83%) and high-intermediate endemicity (5.00% -7.99%) in countries of the Western Pacific region (about 5.25%) (Figure 1) [10,11]. In contrast, low HBsAg prevalence (< 2.00%) was observed in most countries of the Americas (except Haiti) and Western Europe as well as in Australia and Japan of the Western Pacific region [11].…”
Section: Global Impact and Epidemiology Of Hepatitis B Virus (Hbv) In...mentioning
confidence: 99%
“…After treatment with U18666A, the levels of Alix and Tsg101 in the exosome fractions 6-8 were reduced (Figure19B). Following U18666A treatment, the viral DNA (Figure19A) and HBcAg (Figure19B) present in fractions 6-8 nearly disappeared completely, and instead were concentrated in fractions10, 12 (viral DNA) and in fractions 10 and 11 (HBc antigen).…”
mentioning
confidence: 99%